Artificial neural network based vibration control of active engine mounting isolation system - Ridhuan Siradj , Fadly Jashi Darsivan; Wahyudi, Martono; Faris, Waleed Fekry; Ata, A.A (2007)
Vibration suppression of engine induced disturbances has been one of the important issues in vehicle comfort. With the trend of lighter vehicles and powerful engine passengers are subjected to vibrations which can have an adverse effect to comfort. These unwanted engine vibrations need to be reduced if comfortability is one of the main priorities. In this paper neural network predictive controller is used to isolate the vibrations induced from the engine to the chassis. The engine is modeled as two degrees of freedom vibration system and the foundation is assumed to be rigid. The source of the engine disturbances will be represented as the bounce and pitch. A mathematical simulation is done to compare the uncontrolled and controlled response of the system. The result obtained shows an improvement to the system response up to a certain level of satisfaction.